PNEUMOCYSTIS PNEUMONIA: CLINICAL AND LABORATORY DIAGNOSTIC ALGORITHM - Berdiyarova Shohida Shukurullayevna; Murtazayeva Nasiba Komiljonovna (Journal of new century innovations, 2023)
Pneumocystosis is one of the most common infections in the world and the importance of this problem has been increasing in recent years. Numerous studies on pneumocystic infection in patients with various pathologies indicate that pneumocystosis is widespread everywhere.